Order Management with Point of Sale (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Order management with point-of-sale (POS) is typically used to manage the sales and orders in the restaurant. It includes hardware components such as computers to function as a POS system. When a customer arrives at a POS counter by purchasing an order, the cashier will start a new sales transaction and type the item number; it will retrieve the name and the price of the goods. After purchasing the order, the customer will pay the total amount of his/her order. After the payment, the customer will receive a receipt from the counter. The agile scrum method is proven effective throughout the research made by the researchers. Through the use of the agile scrum method, our research became consistent and accurate and has produced results exactly what the product owner and the team wanted. As the process started at the order management with POS, the system evaluated and made orders. The kitchen cooked the order for thecustomer punched by POS. It will show or display it in order breakdown. The kitchen may cook it depending on the ingredient inside the storage room, and the order depends if it is pending or ready to serve. If the kitchen and bar are out of stock inside the storage room, then the kitchen may request inventory management items. Inventory management may receive it and show it in the request frame. If the inventory is out of stock, then the inventory will request to the warehousing for the items, ingredients, or other equipment that is needed for the integration. Meanwhile, food and beverages costing are managed to compute and analyze the gathered data to analyze the goods and ingredients used. Food cost will be displayed on the menu in the POS after food costing. The restaurant analytics is responsible for the printed report of the restaurant, and analytics is responsible for displaying the data by using the dashboard for what was the most sold item within the POS. The total revenue gathered by the restaurant, total ID inside POS, inventory data, food costing, and kitchen total wasted items were determined. The researchers and developers also met the expectations of the product owner by fulfilling his request and discussed other parts of the system that can be improved and change according to what the product owner desires. The researchers gave each other’s roles to each module to fill the gap and waste no time in developing and improving each module.
Keywords: point of sale